AtPAP1 Interacts With and Activates SmbHLH51, a Positive Regulator to Phenolic Acids Biosynthesis in Salvia miltiorrhiza - Wu, Yucui; Zhang, Yuan; Li, Lin; Guo, Xiaorong; Wang, Bin; Cao, Xiaoyan; Wang, Zhezhi (Frontiers in Plant Science, 2018)
Phenolic acids from Salvia miltiorrhiza have drawn considerable attention in recent years because of their remarkable pharmacological activities. We previously reported that Arabidopsis thaliana transcription factor production of anthocyanin pigment 1 (AtPAP1) has strong capability to promote the production of phenolic acids in S. miltiorrhiza. However, the responsible molecular mechanism is unclear. Here, we analyzed the transcriptome of transgenic S. miltiorrhiza that over-expressed AtPAP1. Transcriptome analysis revealed 4152 genes that were differentially expressed due to ectopic AtPAP1 overexpression. SmbHLH51, a novel bHLH gene significantly up-regulated by constitutive expression of AtPAP1, was isolated from S. miltiorrhiza for detailed functional characterization. SmbHLH51 localizes in the nuclei and interacts with AtPAP1, indicating that they probably comprise a regulatory transcription complex. Enhanced or reduced expression of SmbHLH51 was achieved in S. miltiorrhiza by gain- or loss-of-function assays, respectively, revealing that SmbHLH51 is a positive transcriptional regulator of the pathway for phenolic acid biosynthesis. We propose that applying this functional genomics approach through the transcriptomic analyses is an efficient means for identifying novel genes involved in plant secondary metabolism.